Transfuges de classes et représentation de la mobilité sociale - Laélia Véron (Contextes, 2025)
When we think of “class defectors stories”, we most often think of a particular type of narrative that describes, in a more or less tormented way, an intellectual social climbing, focusing on school and often ending with access to writing or public speaking. This type of narrative has become a literary canon that reductively standardizes our vision of social mobility. Therefore, this article tries to explore narratives that do not correspond to this canon (in particular the narratives of economic class defectors) to better situate the literary class defector narrative in relation to traditional narratives of social mobility (self made man, fairy tale) and thus be able to question its sociological relevance and political significance.